Hubungan Kecemasan Berkomunikasi dan Percaya Diri Dengan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas XI SMA Negeri 2 Pematangsiantar - Melda Hotnisari Hutagaol; Binsar Tison Gultom; Sotarduga Sihombing (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to prove the relationship between communication and self-confidence with the Economics learning outcomes of class XI students at SMA Negeri 2 Pematangsiantar. The problem in this research is the high level of student communication anxiety in class which is shown through behavior such as being embarrassed to ask the teacher, having difficulty expressing opinions, avoiding speaking in front of the class.This type of research is descriptive quantitative research. The population in this study were students in classes XI-8, XI-9, XI-10 in Economics subjects at SMP Negeri 2 Pematangsiantar with a total of 106 students. The sample in this study consisted of 106 people using a saturated sampling technique with sample determination if all members of the population were used as samples.Based on the results of descriptive analysis, it shows that: (1) there is a negative relationship between communication anxiety and Economics learning outcomes in class XI SMA Negeri 2 Pematangsiantar. This is indicated by the Rcount coefficient value - 0.164 which is smaller than the Rtable value of 0.1891. (2) there is a positive relationship between self-confidence and Economics learning outcomes in class XI SMA Negeri 2 Pematangsiantar. This is indicated by the Rhitumg coefficient value of 0.152 which is smaller than the rtable value of 0.189. (3) there is a positive and significant relationship between communication anxiety and self-confidence and the economic learning outcomes of class Xl students at SMA Negeri 2 Pematangsiantar. This is indicated by the Rcount of 0.194 which is greater than the Rtable of 0.1891. The results of this study show that there is a significant relationship between communication anxiety and self-confidence and students' Economics learning outcomes.